Underetanding and using of english grammar - Azar, Betty Schrampfer (Nxb.Tp. Hồ Chí Minh, 2001)
A classic developmental skills text for intermediate to advanced students of English, Understanding and Using English Grammar is a comprehensive reference grammar as well as a stimulating and teachable classroom text.